Synthesis and in vitro anti-proliferative activity of some novel isatins conjugated with quinazoline/phthalazine hydrazines against triple-negative breast cancer MDA-MB-231 cells as apoptosis-inducing agents. (1st January 2017) - Eldehna, Wagdy M.; Almahli, Hadia; Al-Ansary, Ghada H.; Ghabbour, Hazem A.; Aly, Mohamed H.; Ismael, Omnia E.; Al-Dhfyan, Abdullah; Abdel-Aziz, Hatem A.
Abstract: Treatment of patients with triple-negative breast cancer (TNBC) is challenging due to the absence of well- defined molecular targets and the heterogeneity of such disease. In our endeavor to develop potent isatin-based anti-proliferative agents, we utilized the hybrid-pharmacophore approach to synthesize three series of novel isatin-based hybrids5a –h, 10a –h and13a –c, with the prime goal of developing potent anti-proliferative agents toward TNBC MDA-MB-231 cell line. In particular, compounds5e and10g were the most active hybrids against MDA-MB-231 cells (IC50 = 12.35 ± 0.12 and 12.00 ± 0.13 μM), with 2.37- and 2.44-fold increased activity than 5-fluorouracil (5-FU) (IC50 = 29.38 ± 1.24 μM). Compounds5e and10g induced the intrinsic apoptotic mitochondrial pathway in MDA-MB-231; evidenced by the reduced expression of the anti-apoptotic protein Bcl-2, the enhanced expression of the pro-apoptotic protein Bax and the up-regulated active caspase-9 and caspase-3 levels. Furthermore, 10g showed significant increase in the percent of annexin V-FITC positive apoptotic cells from 3.88 to 31.21% (8.4 folds compared to control).